Factors Associated with Incomplete Electronic Medical Records by Nurses after the Transition from Manual Documentation - Dewi, Hesti Puspita; Maryana, Maryana; Hermain, Hermain (Inspirasi Foundation, 2025)
Introduction: Electronic medical records are a crucial part of healthcare. Nursing staff have a crucial responsibility to document all nursing actions or care provided to patients. Incomplete medical records can impact the quality of care and patient safety. Objective: The purpose of this study was to determine factors associated with incomplete electronic medical records by nurses following the transition from manual documentation. Method: This type of research was conducted with a cross-sectional design through a quantitative method approach. The population in this study were all nurses in the inpatient ward at Dr. (H.C) Ir. Soekarno Regional General Hospital in 2025 with a total of 160 nurses and a sample of 125 people. The sampling technique used in this study was the Non-Probability Sampling Technique with the Quota Sampling method. Data analysis used univariate analysis and bivariate analysis with the chi-square test with a 95% confidence level (α = 0.05). Result: This study shows that there is a relationship between workload (p = 0.033, POR = 2.526), motivation (p = 0.003 and POR = 5.238) and attitude (p = 0.004, POR = 3.441) with incomplete electronic medical records by nurses after the transition to manual documentation. In the variables of age (p = 0.210) and length of service (p = 0.127) it was concluded that there was no relationship with incomplete electronic medical records by nurses after the transition to manual documentation. Conclusion: The suggestion from this study is the importance of maintaining and improving nurse motivation, maintaining nurse attitudes, regulating the distribution of nurse workload in inpatient rooms and conducting a refresher regarding the use of electronic medical records in the hospital environment.